Increasing the efficiency of heat utilization of exhaust air from combustion chambers by conversion into electrical energy - Zablodskyi, M.; Kovalchuk, O. (Energy and Automation, 2025)
The article is devoted to solving the urgent problem of increasing the energy efficiency of thermal processes by implementing the latest technology using thermoelectric modules as an alternative source of electricity that uses waste heat. The purpose of the study is to develop and experimentally verify the operability of an autonomous system for recovering heat losses from the combustion chamber of hydrocarbon-water mixtures based on thermoelectric generators. The experimental setup included a commercial module TEC1-12715, which at a temperature gradient of ≈40°C (141°C / 101°C) generated a voltage of 1.56V and a current of ≈0.32A, which corresponds to a power of ≈0.49W. A DC-DC converter (2V → 24V) was used to increase the voltage. The practical suitability of the system was tested on the example of powering a low-power electrical load. The temperature field was assessed during the experimental study using thermal imaging measurements and a non-contact thermometer. A three-dimensional model of ten pairs of P/N-Type elements was developed, which takes into account thermal conductivity and thermoelectric effects. To assess the efficiency of the module, numerical simulation was performed in COMSOL Multiphysics, where a three-dimensional model of an element with 10 thermocouples was created. Under similar temperature conditions, it provided an output voltage of 0.144V. Extrapolation to a full module with 127 pairs gave a theoretical value of ≈1.83V, which is ≈14.7% higher than the experimental results. The discrepancy is explained by thermal losses and idealized modeling conditions. The results obtained confirm the potential of TEG for utilizing low-potential heat and powering auxiliary devices in autonomous power systems. Prospects for further development of the system include the use of materials with a higher Seebeck coefficient; improvement of the cooling system, in particular with the use of CFD analysis; implementation of buffer energy storage for pulsed power supply of loads. Key words: thermoelectric generators, heat recovery, heat loss utilization, water-hydrocarbon mixtures, boost converter, combustion chamber, COMSOL Multiphysics software environment, temperature gradient